Selenium‐Containing Type‐I Organic Photosensitizers with Dual Reactive Oxygen Species of Superoxide and Hydroxyl Radicals as Switch‐Hitter for Photodynamic Therapy - Haiyang Wang; Tian Qin; Wen Wang; Xie Zhou; Faxu Lin; Guodong Liang; Zhiyong Yang; Zhenguo Chi; Ben Zhong Tang (Advanced Science, 2023)
Abstract Organic type‐I photosensitizers (PSs) which produce aggressive reactive oxygen species (ROS) with less oxygen‐dependent exhibit attractive curative effect for photodynamic therapy (PDT), as they adapt better to hypoxia microenvironment in tumors. However, the reported type‐I PSs are limited and its exacted mechanism of oxygen dependence is still unclear. Herein, new selenium‐containing type‐I PSs of Se6 and Se5 with benzoselenadiazole acceptor has been designed and possessed aggregation‐induced emission characteristic. Benefited from double heavy‐atom‐effect of selenium and bromine, Se6 shows a smaller energy gap (ΔEST) of 0.03 eV and improves ROS efficiency. Interestingly, type‐I radicals of both long‐lived superoxide anion (O2•‾) and short‐lived hydroxyl (•OH) are generated from them upon irradiation. This may provide a switch‐hitter of dual‐radical with complementary lifetimes for PDT. More importantly, simultaneous processes to produce •OH are revealed, including disproportionation of O2•‾ and reaction between excited PS and water. Actually, Se6 displays superior in–vitro PDT performance to commercial chlorin e6 (Ce6), under normoxia or hypoxia. After intravenous injection, a significantly in–vivo PDT performance is demonstrated on Se6, where tumor growth inhibition rates of 99% is higher than Ce6. These findings offer new insights about both molecular design and mechanism study of type‐I PSs.